The Effect of Powder-to-Flux Ratio and Heating Duration on the Microstructure and Corrosion Resistance of WO3 Nanoparticle-Reinforced Sn–20Bi Coatings on Low-Carbon Steel - Naglaa Fathy; Mohamed Ramadan; Shereen Mohammad Al-Shomar; Khalid M. Hafez; El-Sayed M. Sherif; Alhulw H. Alshammari; K. S. Abdel Halim (Crystals)
The current research introduces a cost-effective thermal coating process using a tinning surfacing technique to synthesize WO3 nanoparticle-reinforced Sn-20Bi (S20B) alloy coating on low-carbon steel (LCS). A ball-milling machine was used for mechanical mixing and blending of Sn and Bi powders together with 0.25 wt.% WO3 nanoparticles. The produced powders were mixed with a prefabricated flux in two different ratios to optimize the best surface coating morphology. The synthesized coatings were spread out on the surface of the LCS in a layer of 0.25 g cm−2 and were heated for 3, 4, and 5 min at 370 °C. A series of corrosion tests was carried out to understand the effect of the different S20B and S20B-WO3 coatings on the corrosion passivation of the LCS samples in 3.5% NaCl solution. The coating surface layer thickness increased by decreasing the percentage of flux in the synthesized coating. Increasing the heating time (from 3 min to 5 min) increases surface coating uniformity and slightly boosts the average Fe−Sn intermetallic (IMC) layer thickness (from 1.7 ± 0.3 µm to 3.3 ± 0.3 µm). By incorporating 0.25 wt.% WO3 nanoparticles into the S20B coating surface layer, a uniform microstructure was achieved and the thickness of the Fe–Sn IMC layer was reduced to 2.6 ± 0.3 µm. This study found that the presence of WO3 nanoparticles significantly improved the corrosion resistance of S20B-coated LCS. These results demonstrate that adding a small of WO3 nanoparticles significantly enhances the microstructural integrity and corrosion resistance of S20B coatings on LCS.